Living on the Margins : Undocumented Migrants in a Global City - Bloch, Alice, 1964- (Book collections on Project MUSE., 2017)
"Living on the margins offers a unique insight into the working lives of undocumented (or 'irregular') migrants living in London, and their employers. Breaking new ground, this topical book exposes the contradictions in policies, which marginalise and criminalise these migrants, while promoting exploitative labour market policies. However, the book reveals that the migrants can be active agents in shaping their lives within the constraint of status. Taking an inter-disciplinary approach, this fascinating book offers an international context to the research and provides theoretical, policy and empirical analyses. It will appeal to undergraduate and postgraduate students, researchers and academics, as well as policy makers, practitioners and interested non-specialists."--Page 4 de la couverture.